Islam, Democracy, and Digital Religious Influencers: Reconfiguring Political Authority in Contemporary Indonesia - Nadia Kirana Puspitasari; Muhammad Abdullah Mhd Ibrahim; Bambang Narendra Putra (Indonesian Political Transformation, 2026)
Digital media has transformed the relationship between religion, politics, and public authority by enabling religious influencers to shape political discourse beyond traditional institutional structures. In Indonesia, the world's largest Muslim-majority democracy, digital religious influencers have become increasingly influential during elections, policy debates, and discussions concerning national identity. However, existing literature has primarily focused on conventional religious organizations, leaving the political significance of digital religious authority insufficiently explored. This study examines how digital religious influencers reshape political authority, democratic participation, and public opinion in contemporary Indonesia. Drawing upon theories of digital religion, political communication, and democratic governance, the research employs qualitative content analysis of social media platforms, complemented by interviews with religious scholars, digital content creators, policymakers, and civil society organizations. The findings suggest that digital platforms decentralize religious authority by enabling new actors to mobilize political support, frame policy debates, and influence electoral preferences independently of established institutions. At the same time, algorithm-driven visibility and online polarization create new governance challenges related to misinformation, identity politics, and democratic deliberation. The article argues that Indonesia represents an important case for understanding how digitalization transforms religious authority within democratic systems across the Global South. The study contributes to comparative scholarship by proposing a conceptual framework linking digital religious authority, political legitimacy, and democratic resilience. It concludes that effective democratic governance increasingly requires policies that promote digital literacy, transparent platform governance, and inclusive civic engagement while safeguarding religious freedom and democratic pluralism.